Bureaucracy in education - Abd Razak, Dzulkifli (2005)
THE recent Global Competitiveness Report (GCR) 2005 released by the World Economic Forum ranks Malaysia rather well. Malaysia was placed 24th in growthcompetitiveness among 117 nations, up seven places from the previous ranking. This is in contrast to an earlier ranking by The Institute for Management Development’s World Competitiveness Yearbook 2005, where Malaysia was placed about halfway among 60 countries. More specifically, the GCR 2005 ranking puts Malaysia’s spending as the secondleast wasteful country after Singapore, whereas Finland was 10th, United States 20th and Japan 68th. This is consistent with the 2006 Budget emphasis in advocating a more prudent general spending so that Malaysia can secure a better position in future rankings.